Penentuan Guru Piket Dengan Metode Simple Additive Weighting (SAW) - Nur Arafah (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2022)
The problem of decision making is basically a form of selecting from a variety of alternative actions that may be chosen which process through a certain mechanism, with the hope that it will produce the best decision. The preparation of a decision method is a way to develop logical relationships that underlie decision issues into a mathematical method, which reflects the relationships that occur between the factors involved, so that the decision process must be taken through a gradual, systematic, consistent and endeavored process. in every step from the beginning has included and considered various factors. The model used in this decision support system is SAW, because this SAW was chosen because it can determine the weight value for each attribute, then proceed with a ranking process that will select the best alternative from a number of alternatives, in this case the alternative in question is the result of a system based on criteria. - specified criteria.